2021
DOI: 10.1002/rcm.9152
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the deprotonation site of dehydroandrographolide with electrospray ionization mass spectrometry by deuteration

Abstract: Rationale Dehydroandrographolide (DA) is a diterpene compound of biological interest that contains one α,β‐unsaturated lactone group and two hydroxy groups. In the ESI (electrospray ionization) negative ion mode mass spectral analysis of 15‐dideuterodehydroandrographolide (15‐D2‐DA), the deuterium nucleus at the γ position of the α,β‐unsaturated lactone was more easily dedeuterated than deprotonation of the protons from the hydroxy groups. Exploring the rationality of deuteration as a tool for deprotonation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Deh's pharmacological effect is considered stronger than that of Andrographis paniculata (Burm.f.) Wall in some aspects ( Huo et al, 2021 ). Several experiments have confirmed that Deh has pharmacological effects, such as anti-inflammatory and antioxidant activities ( Liu et al, 2019b ; Guo et al, 2020 ; Huo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deh's pharmacological effect is considered stronger than that of Andrographis paniculata (Burm.f.) Wall in some aspects ( Huo et al, 2021 ). Several experiments have confirmed that Deh has pharmacological effects, such as anti-inflammatory and antioxidant activities ( Liu et al, 2019b ; Guo et al, 2020 ; Huo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wall in some aspects ( Huo et al, 2021 ). Several experiments have confirmed that Deh has pharmacological effects, such as anti-inflammatory and antioxidant activities ( Liu et al, 2019b ; Guo et al, 2020 ; Huo et al, 2021 ). However, its pharmacological mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%